IMPLEMENTASI IDENTIFIKASI SISTEM METODE BLACK BOX PADA MOTOR DC MENGGUNAKAN CORRELATION ANALYSIS DAN MODEL ARX - Mangkusasmito, Fakhruddin; Tadeus, Dista Yoel; Subari, Arkhan (Vocational School Diponegoro University, 2020)
The identification system is a procedure to obtain a model of a system, then of the model will be validated to see the accuracy of the model is obtained, compared to the input-output results obtained from the experiments. In the identification system itself known two methods, the method of